2000
DOI: 10.1128/jb.182.8.2336-2340.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Requirements of Phage λ Red-Mediated Gene Replacement in Escherichia coli K-12

Abstract: Recombination between short linear double-stranded DNA molecules and Escherichia coli chromosomes bearing the red genes of bacteriophage in place of recBCD was tested in strains bearing mutations in genes known to affect recombination in other cellular pathways. The linear DNA was a 4-kb fragment containing the cat gene, with flanking lac sequences, released from an infecting phage chromosome by restriction enzyme cleavage in the cell; formation of Lac ؊ chloramphenicol-resistant bacterial progeny was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
1
28
1
Order By: Relevance
“…Escherichia coli BW25113 [⌬(araD-araB)567 ⌬lacZ4787(::rrnB-3) lacIp-4000(lacI q ) Ϫ rph-1 ⌬(rhaD-rhaB)568 hsdR514] (4) and BW27784 (BW25113 ⌬araFGH ⌬araEp::P CP18 -araE) (11) were obtained from the E. coli stock center. Strain TP608 (AB1157 ⌬(recC-ptr-recB-recD)::P tac -gam-red-pae-cI822 sulA6209::tet lexA71::Tn5) was kindly provided by A. R. Poteete (20). sulA6209::tet, followed by lexA71::Tn5, was transduced into strain BW27784 by serial P1 transduction using a P1vir lysate grown with strain TP608, as previously described (18).…”
Section: Methodsmentioning
confidence: 99%
“…Escherichia coli BW25113 [⌬(araD-araB)567 ⌬lacZ4787(::rrnB-3) lacIp-4000(lacI q ) Ϫ rph-1 ⌬(rhaD-rhaB)568 hsdR514] (4) and BW27784 (BW25113 ⌬araFGH ⌬araEp::P CP18 -araE) (11) were obtained from the E. coli stock center. Strain TP608 (AB1157 ⌬(recC-ptr-recB-recD)::P tac -gam-red-pae-cI822 sulA6209::tet lexA71::Tn5) was kindly provided by A. R. Poteete (20). sulA6209::tet, followed by lexA71::Tn5, was transduced into strain BW27784 by serial P1 transduction using a P1vir lysate grown with strain TP608, as previously described (18).…”
Section: Methodsmentioning
confidence: 99%
“…This hyper-rec state of a bacterium expressing some of the phage recombination genes (gam, bet, and exo) partially models the conditions which prevail in a phage-infected cell. It has been found that expression in a red ϩ cell of genes from the nin region of the chromosome, including rap, does not further stimulate recombination but makes recombination partially independent of recF, recO, recR, and ruvC (12). In this study we show that the rap gene accounts for some of this activity, complementing the recombination defect of a ruvC mutant.…”
mentioning
confidence: 56%
“…Starting with an E. coli strain bearing a (recC-ptr-recB-recD)⌬:: P tac -gam-betexo-pae-cI substitution as well as deletions of recG and sulA, two isogenic sets of rap ϩ and mutant rap strains with mutations in various other recombination genes were constructed. The reason for employing a background lacking recG is that deletion of recG elevates the frequency of Red-mediated recombination; deletion of sulA was found to enhance the viability of recBCD⌬::red strains lacking recF, recO, or recR function (12). The results of crosses in these strains are summarized in Table 2.…”
Section: Strainsmentioning
confidence: 97%
“…1) as a sole sulfur source, the metA and metB genes were expressed to ϳ100-fold greater levels ( Table 2). To determine if the repression of the metA and metB genes was mediated by the MetJ protein, a metJ::ble mutation-whereby the entirety of the metJ coding sequence is replaced with a cassette expressing a protein conferring zeomycin resistance-was constructed by directed gene knockout (24). As expected, the MetA::LacZ and MetB::LacZ fusion proteins were expressed to high levels in the presence of methionine in a metJ::ble mutant background (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Following amplification of the appropriate antibiotic resistance gene by PCR with these tailed primers, allelic replacement was performed by electroporation of the fragment into a host cell bearing plasmid pTP223 (24), which expresses the red recombinase system. Replacement of the chromosomal gene with the antibiotic resistance gene was confirmed by (i) amplification of the target locus via PCR and determination of the nucleotide sequences of the join points between native chromosomal DNA and the introduced antibiotic resistance genes and (ii) linkage analysis of the antibiotic resistance gene to known neighboring loci via P1 cotransduction assays.…”
Section: Methodsmentioning
confidence: 99%